Navigating the Influence of ChatGPT on the Writing Skill: An Exploratory Narrative Review - Nour El Houda Kherfane; Lamia Belferd (Proceeding of the International Conference on Global Education and Learning, 2024)
Generative Pre-trained Transformer (ChatGPT), is an artificial intelligence (AI) model that has revolutionized the educational landscape in recent years. Its use has been explored across various educational fields; however, given that this AI model is language-based, it has attracted particular interest in language teaching, especially in developing the writing skill. Due to the importance of the writing skill in language learning, and the extensive body of research investigating the best ways to support this skill using ChatGPT, the current study aims to provide an overview of the latest findings regarding the use of ChatGPT in developing writing. Through a narrative literature review approach, this paper will offer comprehensive documentation of the various ways ChatGPT can be used to support the writing skill, as well as the potential risks associated with its implementation. These objectives will be achieved by addressing two key research questions: In what ways can ChatGPT be useful in developing the writing skill? and what are the possible risks of implementing this tool in developing the writing skill? By answering these questions, the paper will help equip educators and learners with a comprehensive understanding of the most effective ways to use this tool to enhance the writing skill.